2019
DOI: 10.1007/s41048-018-0079-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-encapsulation of curcumin and doxorubicin in albumin nanoparticles blocks the adaptive treatment tolerance of cancer cells

Abstract: The adaptive treatment tolerance (ATT) of cancer cells is the main encumbrance to cancer chemotherapy. A potential solution to this problem is to treat cancer cells with multiple drugs using nanoparticles (NPs).In this study, we tested the co-administration of curcumin (Cur) and doxorubicin (Dox) to MCF-7 resistant breast cancer cells to block the ATTand elicit efficient cell killing. Drugs were co-administered to cells both sequentially and simultaneously. Sequential drug co-administration was carried out by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 49 publications
(46 reference statements)
1
41
0
Order By: Relevance
“…There are probably 18.1 million new cancer cases and 9.6 million cancer deaths worldwide in 2018 (Bray et al 2018). No time to lose in the fight against cancer (Motevalli et al 2019;Sun et al 2018). Previous lines of research have reported that bacteria such as Bifidobacterium bifidum and E. coli have ability to target tumor, proliferate in specific tumor cells, and trigger effective antitumor through specific immune factormediated immune response (Kim et al 2015a, b;Pawelek et al 2003).…”
Section: Genetically Engineered Omvs For Cancer Treatmentmentioning
confidence: 99%
“…There are probably 18.1 million new cancer cases and 9.6 million cancer deaths worldwide in 2018 (Bray et al 2018). No time to lose in the fight against cancer (Motevalli et al 2019;Sun et al 2018). Previous lines of research have reported that bacteria such as Bifidobacterium bifidum and E. coli have ability to target tumor, proliferate in specific tumor cells, and trigger effective antitumor through specific immune factormediated immune response (Kim et al 2015a, b;Pawelek et al 2003).…”
Section: Genetically Engineered Omvs For Cancer Treatmentmentioning
confidence: 99%
“…This proved that the hydrogel and the polymer do not have any biocompatibility-related issues and that the empty material does not possess any therapeutic property. Furthermore, the free RESV/DOX (54.97 ± 3.80%)-treated group showed larger necrotic area than the single drug-loaded hydrogel-based treated groups (Na-DOX-hyd-RESV and Na-DOC-hyd+G4.5-DOX), which could mainly be due to systemic toxicity of the freely diffused DOX in the area [ 61 ]. Based on the results of the in vivo model mice study, we concluded that the highest tumor growth inhibition was observed in mice treated with Na-DOX-RESV+G4.5-DOX, as this formulation offers synergistic antitumor effect due to sequential, controlled, and sustained release of the drugs at the tumor sites.…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin showed slower release as compared to doxorubicin, presumably because it is more hydrophobic than doxorubicin. Therefore, curcumin could interact with the domains of albumin more strongly [81,82]. Experimental results exhibited that curcumin and doxorubicin coencapsulated in albumin nanoparticles were able to decrease the ATT effect.…”
Section: Dextran-based Nanoparticles For Cancer Therapymentioning
confidence: 98%
“…On the contrary, if curcumin and doxorubicin were delivered on separate nanoparticles, curcumin would aggregate and be entrapped by lysosomes, making it unable to block P-glycoprotein in the cytosol [83]. As a result, any doxorubicin taken up by the cancer cells would be moved out [81]. Another DDS based on bovine serum albumin nanoparticles for codelivery of doxorubicin and cyclopamine was developed by Lu et al Similar to curcumin, cyclopamine can increase doxorubicin accumulation by inhibiting P-glycoprotein expression [84,85].…”
Section: Dextran-based Nanoparticles For Cancer Therapymentioning
confidence: 99%